Immediate Functional Loading in Posterior Mandible: A Case Report on Flapless Implant Surgery - Gupta, Gaurav; Gupta, D.K; Gupta, Priyanka; Rana, Kuldeep Singh; Shah, Parth; Chandra, Neeraj (Journal of Orofacial Research, 2022)
Edentulous space management has been made easier by dental implants. Patients having sufficient gingival tissue with sufficient bone volume at recipient site are preferred for implant surgery with flapless approach. The aim of our article is to report a case of flapless implant surgery procedure for the management of edentulous space in posterior mandibular area.